2023
DOI: 10.1027/1015-5759/a000698
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Extended Violent Ideations Scale to Measure Both Non-Sexual and Sexual Violent Ideations (The VIS-X)

Abstract: Abstract. A previous study developed and validated a multi-item instrument for the assessment of violent ideations, the “Violent Ideations Scale” (VIS). However, the final 12-item scale contained no items relating to sexual violence and was thus lacking an important dimension of violence. The current study explores an expansion of the original VIS to include ideations of sexual violence and investigates the psychometric properties of this new version: The Violent Ideations Scale-Extended (VIS-X). The VIS-X was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Finally, previous studies (Urruela et al, 2023) have reported the need for evidencebased tools applicable to forensic settings. Although the VIS-ES is still to be tested in Spanish forensic populations, we hope that this tool will enhance the objectivity, transparency, and efficiency of violence risk assessment processes in the future.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Finally, previous studies (Urruela et al, 2023) have reported the need for evidencebased tools applicable to forensic settings. Although the VIS-ES is still to be tested in Spanish forensic populations, we hope that this tool will enhance the objectivity, transparency, and efficiency of violence risk assessment processes in the future.…”
Section: Discussionmentioning
confidence: 94%
“…Second, the VIS-ES does not include any items related to sexual violent thoughts. A recently published extended version of this scale, the VIS-X (Urruela et al, 2023), confirmed that sexual and non-sexual violent thoughts belonged to two different dimensions. Since the VIS-X was developed in parallel to the VIS-ES, we were not able to test the differences across versions.…”
Section: Limitations and Future Directionsmentioning
confidence: 84%
See 1 more Smart Citation
“…One item captured the use of tobacco, 1 captured alcohol use (beer and alcopops), 1 captured alcohol use (spirits) and 1 captured cannabis use. Violent ideations were measured using the expanded Violent Ideations Scale [ 41 , 42 ], capturing fantasies of committing acts of physical, indirect, and sexual violence across 17 items. Aggression was measured using 19 items from the SBQ, covering physical, indirect, proactive, and reactive aggression.…”
Section: Methodsmentioning
confidence: 99%
“…Of this sample, 979 had complete data on the below-described predictors and outcomes. See Table S1 and Table S2 in Multimedia Appendix 1 [32][33][34][35][36][37][38][39][40][41][42][43][44] for the descriptive statistics for these samples.…”
Section: Participantsmentioning
confidence: 99%